Generation mechanism of residual stress at press-blanked and laser-blanking edges of 1.5 GPa ultra-high strength steel sheet. (August 2021) - Mori, Ken-ichiro; Nakamura, Naotaka; Abe, Yohei; Uehara, Yuta
Abstract: The generation mechanism of the residual stress at press-blanked and laser-blanked edges of a 1.5 GPa ultra-high strength martensite steel sheet was investigated. The residual stress at the press-blanked edges of the 1.5 GPa sheet is highly tensile, whereas the residual stress at the laser-blanked edges is compressive. The high tensile residual stress causes the occurrence of hydrogen-induced delayed cracking and the reduction in fatigue strength. In press blanking of the 1.5 GPa sheet, considerably high compressive stress was generated under the punch corner just before the separation due to a small critical punch stroke, and high tensile residual stress on the fracture surface of the blanked edge was induced by releasing this high compressive stress for the separation. Not only the high strength of the 1.5 GPa sheet but also the low ductility influences the generation of the high tensile residual stress on the fracture surface because of the small critical stroke. On the other hand, the compressive residual stress at the laser-blanked edges of the 1.5 GPa sheet was generated by the volume increase of the martensite transformation at a comparatively low temperature. In addition, an approach for determining the allowable amount of hydrogen for the occurrence of delayed cracking at the edges was proposed, and the relationship between the critical residual stress and the amount of hydrogen for the 1.5 GPa sheet was obtained. Graphical abstract: Unlabelled Image Highlights: The generation mechanism of residual stress at blanked edges was investigated. The residual stress at press-blanked edges was tensile due to stress release. Compressive residual stress for laser blanking was due to martensite transformation. Delayed cracks and fatigue strength reduction were caused by tensile residual stress. An approach for determining allowable hydrogen amount was proposed.